Improved L-Asparaginase Properties and Reusability by Immobilization onto Functionalized Carbon Xerogels - Barros, Rita A. M.; Cristóvão, Raquel O.; Carneiro, Inês. G.; Barros, Maria A.; Pereira, Matheus M.; Carabineiro, Sónia A. C.; Freire, Mara G.; Faria, Joaquim L.; Santos-Ebinuma, Valéria C. [UNESP]; Tavares, Ana P. M.; Silva, Cláudia G. (Wiley, 2024)
Enzyme immobilization can offer a range of significant advantages, including reusability, and increased selectivity, stability, and activity. In this work, a central composite design (CCD) of experiments and response surface methodology (RSM) were used to study, for the first time, the L-asparaginase (ASNase) immobilization onto functionalized carbon xerogels (CXs). The best results were achieved using CXs obtained by hydrothermal oxidation with nitric acid and subsequent heat treatment in a nitrogen flow at 600 °C (CX−OX-600). Under the optimal conditions (81 min of contact time, pH 6.2 and 0.36 g/L of ASNase), an immobilization yield (IY) of 100 % and relative recovered activity (RRA) of 103 % were achieved. The kinetic parameters obtained also indicate a 1.25-fold increase in the affinity of ASNase towards the substrate after immobilization. Moreover, the immobilized enzyme retained 97 % of its initial activity after 6 consecutive reaction cycles. All these outcomes confirm the promising properties of functionalized CXs as support for ASNase, bringing new insights into the development of an efficient and stable immobilization platform for use in the pharmaceutical industry, food industry, and biosensors.
Keywords: Adsorption; Bioconjugate; Functionalized carbon xerogels; Immobilization; L-asparaginase